Column Stability under Elastic Support - Higgins, T.R. (Engineering Journal, 1965)
Professor Galambos has shown that the amount of diagonal bracing or masonry wall needed to prevent sidesway of a steel building frame under gravity loading is relatively small. The approach which he used can provide useful stability solutions for (a) frames that depend entirely upon their own bending stiffness for lateral support yet include columns without rigid connections and (b) columns with flexible lateral support. It has been shown that, in elastic frames, the value of the critical gravity load producing incipient sidesway in a rectangular frame is not greatly influenced by concurrent bending stress resulting from moment at the ends of the columns. Hence presence of such stresses will be ignored in the following procedures for designing to prevent premature joint translation.